2016
DOI: 10.1515/cerce-2016-0018
|View full text |Cite
|
Sign up to set email alerts
|

Essential Oil and Microelement Composition of Thymus citriodorus L. and Lippia citriodora H.B.K.

Abstract: Lemon verbena (Lippia citriodora H.B.K., Verbenaceae family) is indigenous to South America and cultivated as an aromatic plant in various parts of world. Lemon thyme (Thymus citriodorus L.), Lamiaceae family, is a perennial medicinal plant native to southern Europe and is cultivated in the Mediterranean region. These species are cultivated mainly for the lemon-like aroma emitted from their leaves due to the presence of dimethyl-2,6- octadienal, also known as lemonal or citral, which is used in food and perfum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…The maximum geraniol content (72.5 %) was observed before flowering, while the minimal content (54.2 %) was detected during the fruiting stages. In a study by Kizil et al, [82] 22 components were identified in EO of T. citriodorus, with trans-geraniol (31.06 %), trans-citral (14.05 %) and cis-geraniol (7.65 %) being the main components. The EO of T. pulegioides EO is predominantly composed of phenolics (38.5 %), thymol being the main component at 26.3 %.…”
Section: Phytochemicals Composition and Nutra-pharmaceutical Potentia...mentioning
confidence: 98%
“…The maximum geraniol content (72.5 %) was observed before flowering, while the minimal content (54.2 %) was detected during the fruiting stages. In a study by Kizil et al, [82] 22 components were identified in EO of T. citriodorus, with trans-geraniol (31.06 %), trans-citral (14.05 %) and cis-geraniol (7.65 %) being the main components. The EO of T. pulegioides EO is predominantly composed of phenolics (38.5 %), thymol being the main component at 26.3 %.…”
Section: Phytochemicals Composition and Nutra-pharmaceutical Potentia...mentioning
confidence: 98%
“…In other studies, Bagdat et al (2011) reported that the essential oil content of T. citriodorus was identified between 1.30 and 1.43%. Kizil and Toncer (2013) determined that the essential oil content of lemon thyme was 0.9%. Table 1 shows the essential oil components obtained from three harvest stages of T. citriodorus and twenty one compounds identified are listed according to their retention indices were found in the oils (Fig.…”
Section: Introductionmentioning
confidence: 99%